Adaptive Education in the Era of Society 5.0: Integration of Digital Literacy Technology and Humanistic Values - Suwarma, Dina Mayadiana; Jenuri, Jenuri (PT. Hafasy Dwi Nawasena, 2025)
Abstract This study discusses the concept of adaptive education in the context of Society 5.0 by emphasizing the integration of technology, strengthening digital literacy, and internalizing humanistic values as the foundation for forming a human-centered education ecosystem. Through a qualitative descriptive approach based on literature review, this study synthesizes various theories and empirical findings to formulate a conceptual framework of adaptive education that is relevant to the demands of the digital age. The results show that adaptive education can only be realized if technological innovation is balanced with critical digital literacy skills and humanistic values that serve as a moral compass in the use of technology. Technology plays a role in increasing the flexibility and personalization of learning, but its success is highly dependent on the readiness of educators and students in pedagogical and ethical aspects. This article contributes novelty through the integration of the three main pillars of technology, digital literacy, and humanistic values into a single conceptual framework to build sustainable and future-oriented education.